Influence of 10 nm Hole and Electron Transport Layers on Enhancing the Efficiency of Elpasolite Solar Cell (ESC) With Dual Light Active Layers for Nanostructured Photovoltaic Applications - G. P. S. Prashanthi; Umakanta Nanda (IEEE Access, 2024)
Elpasolites are expected to be promising photovoltaic semiconductor alternatives to lead-based perovskite semiconductors. Concern over the stability and toxicity of lead halide perovskites has led to an increase in interest in the environmental friendly elpasolite Cs2BiAgI6 (Cesium Bismuth Silver Iodide). An extensive numerical analysis of the Cs2BiAgI6 based elpasolite solar cell (ESC) model with the standard n-i-p nanostructured planar architecture ITO/TiO2/Cs2BiAgI6/CIGS/NiO/Au is presented in this article. Numerous device parameters, such as temperature, series resistance, thickness and the defect density of the dual-graded light absorber layers, electron transport layer (ETL), and hole transport layer (HTL), have all been thoroughly studied. The device numerical modeling and simulation is carried out using the well-known SCAPS-1D simulation tools (version 3.3.10). Under AM1.5G illumination, achieved a Voc of 1.2277 V, Jsc of 34.342 mA/cm2, and fill factor of 86.25% with power conversion efficiency of 36.36% through parameter optimization, which is much higher than the highest reported values found in the literature.